A study on Factors associated with non-disclosure of HIV positive status to sexual partners by adult patients attending the VCT clinic at Nhlangano health centre, Swaziland. - Legasion, Michael (University of Limpopo (Medunsa Campus), 2010)
A study on Factors associated with non-disclosure of HIV positive status to sexual partners by adult patients attending the VCT clinic at Nhlangano health centre, Swaziland. Aim: To describe the factors associated with non-disclosure of known HIV sero-positive status to sexual partners by adult patients attending the VCT clinic at Nhlangano health center, Swaziland. Design:- Cross-sectional study using questionnaire administered by a trained research assistant. Setting:- Nhlangano health center VCT clinic, Nhlangano town in the Shiselweni region, Southern Swaziland. Study population:- All adult patients above the age of 18 years who had undergone HIV testing, who knew their positive HIV status and had follow up visits at the VCT clinic of Nhlangano health centre, from November 2005 (when the centre started rendering VCT service) till the beginning of the data collection, in September, 2008. Results:-The vast majority (89.1%) disclosed their positive HIV status to their sexual partners and 94.6% believed that letting their sexual partner/s know about their HIV status was very important. In terms of knowing the HIV status of their partners, 55.4% knew the HIV status of all of their sexual partners and 44.6% knew only the status of the regular partner/s. With regard to condom use, 96.7% believed that using condoms helps them to prevent transmission of HIV and 91.3% expected that letting their partners know about their HIV status would help them use condom IV more frequently. Only 53.3% said they would insist on condom use even if their partner is not willing to use. Conclusion:-  The rate of positive HIV status disclosure to sexual partner found in this study compared to many studies done in other settings is considerably high. This is encouraging especially considering the existing very high prevalence of HIV infection in the country. Despite this though, knowing partner's HIV status was relatively lower. Therefore, people are more likely to share their HIV status with a partner than insist that the partner does the same.  Even though the study was done only amongst patients attending VCT, it is important to note that the majority of the patients had positive attitudes about HIV status disclosure to a partner, and believed in the importance of letting their sexual partner/s know about their HIV status. Patients understood the unethical nature of engaging into sexual intercourse without disclosing their positive HIV status to their partner. It is possible to conclude that factors which contributed to these positive results should be implemented at a larger scale, namely creating awareness, health education, good counseling and follow up of treatment.  Awareness of the importance of condom use in preventing HIV transmission (including the fact that disclosure of HIV status to a partner enhances its better use) was impressively high amongst almost all participants. But it is worrisome that only half of the participants said they would insist on condom use irrespective of their partners’ willingness to use it or not. V  The variables that were found to be independently associated with disclosure to a partner comparing those who disclosed with those who did not were gender, age, marital status, education, number of sexual partners, and stage of the HIV condition.
Thesis (M. Med.(Family Medicine))--University of Limpopo (Medunsa Campus), 2010.
Keywords: HIV; Acquired immunodeficiency syndrome